Influence of small lanthanum additions on the structural and electromagnetic properties of lithium ferrite; VI International Baltic Conference on Magnetism 2025 (IBCM 2025) - Elkina Yuliya Sergeevna Yu. S. (2025, 2025)
Заглавие с экрана